T Cell Metabolism in Infection - Wik, Jonas Aakre; Skålhegg, Bjørn Steen (Frontiers in Immunology, 2022)
T lymphocytes (T cells) are divided into two functionally different subgroups the CD4+ T helper cells (Th) and the CD8+ cytotoxic T lymphocytes (CTL). Adequate CD4 and CD8 T cell activation to proliferation, clonal expansion and effector function is crucial for efficient clearance of infection by pathogens. Failure to do so may lead to T cell exhaustion. Upon activation by antigen presenting cells, T cells undergo metabolic reprograming that support effector functions. In this review we will discuss how metabolic reprograming dictates functionality during viral infections using severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and human immunodeficiency virus (HIV) as examples. Moreover, we will briefly discuss T cell metabolic programs during bacterial infections exemplified by Mycobacterium tuberculosis (MT) infection.